Ochrona tajemnicy adwokackiej a usługi świadczone w chmurze obliczeniowej: [Protection of legal privilege in the cloud computing] (Studia Prawnicze / The Legal Studies, 2017)
Wykonywanie zawodów prawniczych nierozerwalnie wiąże się z obowiązkiem dochowania tajemnicy zawodowej. W szczególności praca adwokata i radcy prawnego, polegająca na świadczeniu pomocy prawnej, wiąże się z podwyższonymi standardami w zakresie ochrony powierzonych informacji. The article presents most important issues related to cross-border processing of lawyers data containing professional secrets, including the processing of personal data. Author discusses risks associated with the lack of standardization in the area of protection of legal priviledge in cloud computing services in different jurisdictions, also between EU Member States. Article is supplemented by an analysis of terms of service and privacy policies of the largest providers of services in the public cloud (Google, Microsoft) in the context of the fulfillment of the legal requirements for the protection of personal data and the professional secrecy.